2020
DOI: 10.2478/mgr-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective and prospective view of current and future population ageing in the European Union 28 countries

Abstract: Population ageing in the EU28 is an important twenty-first century phenomenon, affecting virtually every aspect of life in these countries. The results of the latest EUROPOP2018 population forecast indicate that the rate of ageing is accelerating. The aim of this paper is to analyse the current level of population ageing in the EU28, identify spatial differences, and point to likely trends by the middle of this century. For these purposes, we have used a combination of conventional chronological indicators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Moravian geographical reports expectancy, so future seniors in 2040 could face nearly 18 years for men and more than 21 years for women (Šprocha and Ďurček, 2019). The situation is similar in the neighbouring Czech Republic, Poland and Hungary and other post-socialist countries (Kačerová et al, 2012;Šidlo et al, 2020).…”
Section: Introductionmentioning
confidence: 78%
“…Moravian geographical reports expectancy, so future seniors in 2040 could face nearly 18 years for men and more than 21 years for women (Šprocha and Ďurček, 2019). The situation is similar in the neighbouring Czech Republic, Poland and Hungary and other post-socialist countries (Kačerová et al, 2012;Šidlo et al, 2020).…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, the Chinese government cannot ignore the public debt caused by the aging population. In addition, Cooley et al [21], Pascual-Saez et al [22], S ˇı ´dlo et al [23], and Bobeica et al [24] have confirmed that the aging population would cause total savings to decrease, inflation and other things that would hold back the economy. Through the above literature, it can be found that the impact of the aging population on developed countries or regions is negative.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Thus, not all older persons are dependent and frail, much less of the young olds who have turned 65 only in recent years. As Šídlo et al (2020) have shown, over time and space, the old age threshold cannot simply be seen in fixed terms as the number of years already lived (chronological age). The number of years remaining in life is a much more important indicator regarding ageing (Howdon & Rice, 2018; Sanderson & Scherbov, 2010).…”
Section: Pandemic Exacerbates Ageismmentioning
confidence: 99%